DECISION OF MA 3180/K / PDT/2019 (LEGAL ANALYSIS OF THE SALE AND PURCHASE OF JOINT PROPERTY PRE-DIVISION BY THE TEMPORARY LAND DEED OFFICER) - Febrianty, Yenny; Kumala, Brik; Flora, Henny Saida; Setiawan, Beni (Gorontalo Law Review, 2024)
As stated in Article 36 of Law No. 1 of 1974 respecting joint marriage, any spouse may operate on joint property with a permission. Investigating Supreme Court decision number 3180 K/PDT/2019—which deals with the sale and purchase of undivided joint property in the presence of the temporary land deed officer (PPAT)—and its legal implications is the goal of this research. This study uses conceptual, case, and legislative methods, and it is normative in character. Primary and secondary sources of law are consulted. Legal material analysis is an approach that uses a procedure that is prescriptive. In accordance with the results of the investigation, it is illegal for the PPAT to have issued a deed of sale and purchase and for M.Uzer and Deslina to have sold shares without Herlina's knowledge or approval. Given that the property being sold is still jointly owned, the sale and purchase are declared unlawful according to MA RI No. 701K/PDT/1997. As a consequence, the deed of sale and purchase is legally flawed, and the Certificate of Property Rights in Deslina's name is no longer enforceable.